Competing in several areas simultaneously: The case of strategic asset markets - Manfred Nermuth (Games, 2011)
We characterize the structure of Nash equilibria for a certain class of asset market games. In equilibrium, different assets have different returns, and (risk neutral) investors with different wealth hold portfolios with different structures. In equilibrium, an asset's return is inversely related to the elasticity of its supply. The larger an investor, the more diversified is his portfolio. Smaller investors do not hold all the assets, but achieve higher percentage returns. More generally, our results can be applied also to other 'multi-market games' in which several players compete in several arenas simultaneously, like multi-market Cournot oligopolies, or multiple rent-seeking games.
Keywords: 330; asset markets; Nash equilibrium; multigames